Damned if you don't: Public perceptions of polygraph testing and suspect willingness to be tested - Barnes, Bryan (Legal and criminological psychology, 2025)
Purpose Information about whether an individual volunteered to take or refused to take a polygraph test may become public knowledge, and in some instances, becomes known to jurors. While numerous studies have investigated how the public regards polygraph test accuracy, little is known about public perceptions surrounding refusal or willingness to take a polygraph test in cases where an individual's veracity is questioned. Methods An online survey of 302 individuals assessed beliefs about the accuracy of polygraph tests and trust in denials of guilt in hypothetical cases where a polygraph test was: (1) refused, (2) voluntarily taken with no results, (3) voluntarily taken and passed and (4) voluntarily taken and failed. Results Overall, the average rating of polygraph accuracy in detecting deception was 71%, and 67% for detecting truthfulness. The findings also indicate that suspect willingness to take a polygraph test significantly increases trust in their denial of guilt, while refusal to take the test is perceived similarly to a failed test. Despite scepticism about the accuracy of polygraph tests, willingness or refusal to take the test impacts whether the suspect is trusted by others. Conclusions For courts in which polygraph test evidence is inadmissible, jurors should not be informed about whether the defendant or any witness offered or refused a polygraph test because they are likely to judge truthfulness based on this information.